Experimental Investigation of the Effect of a Combination of Active and Passive Cooling Mechanism on the Thermal Characteristics and Efficiency of Solar PV Module - Ephraim Bonah Agyekum; Seepana PraveenKumar; Naseer T. Alwan; Vladimir Ivanovich Velkin; Sergey E. Shcheklein; Salam J. Yaqoob (Inventions, 2021)
A photovoltaic (PV) module’s electrical efficiency depends on the operating temperature of the cell. Electrical efficiency reduces with increasing PV module temperature which is one of the drawbacks of this technology. This is due to the negative temperature coefficient of a PV module which decreases its voltage significantly while the current increases slightly. This study combines both active and passive cooling mechanisms to improve the electrical output of a PV module. A heat sink made up of aluminum fins and an ultrasonic humidifier were used to cool the panel. The ultrasonic humidifier was used to generate a humid environment at the rear side of the PV module. The cooling process in the study was able to reduce the temperature of the panel averagely by 14.61 °C. This reduction led to a 6.8% improvement in the electrical efficiency of the module. The average power of 12.23 W was recorded for the cooled panel against 10.87 W for the referenced module. In terms of water consumption, a total of 1.5 L was approximately consumed during the whole experimental process due to evaporation. In effect, the proposed cooling approach was demonstrated as effective.